Overcoming Failure in the Design and Implementation of Public-Private Partnership Projects: Lessons from the Lekki Toll Road Concession - Nwangwu, George (Journal of Sustainable Development Law and Policy, 2025)
At its inception, the Lekki toll road project was touted as the landmark public-private partnership (PPP) project in Nigeria and even in West Africa. The project was lauded for its status as the first road sector PPP project in Nigeria and anticipated to become the template for future PPP projects across the country. However, the project failed and the Lagos State Government had to buy back the concession from the private sector concessionaire. This article evaluates why the project failed through the lens of risk management. This is based on the theoretical premise that the most critical success factor for PPPs is proper risk allocation and management. Therefore, where risks are not properly identified, allocated and mitigated, it most likely leads to project failure. Consequently, using a case study methodology, this article examines how different project risks were managed in the Lekki toll road project, to identify why it failed. The study concludes that while financial, construction and currency risks were managed to varying degrees with limited success, the management of stakeholder opposition risk failed completely. It is believed that the lessons learned from this study will help in designing better PPP projects in Nigeria.